Analysis of Human Resources Readiness through ADKAR, Management Commitment and Specific Competence Approach in Support Transformational Era PT KAI - Febriwan, Muhamad; Bangun, Yuni Ros (The Indonesian Journal of Business Administration, 2013)
PT Kereta Api Indonesia performs the transformation towards the service orientation in order to keep survive in its business environment. Human resources readiness of supporting the transformation is determinative without it, the company will fail in transformation and pursuing the business target. This applied ADKAR (awareness, desire, knowledge, ability and reinforcement), management commitment (organization support, reward, empowerment and training) and specific competencies (hospitality competencies based benchmarking results) and (5 based values as competencies). As an approach to analyze human resources readiness variables of behavior to change that consist of consists of the belief, attitude and motivation were tested and analyzed by applying path analysis model. Path analysis showed that the two factors had strong relations with behavior toward change, and that ADKAR and specific competencies (5 based values) were highly influential.  Descriptive analysis and path coefficient matrix led to discovery among the three factors should be considered by management of PT KAI to prevent failure in transformation. The indicators should be improved, developed and maintained to stimulate the person’s readiness of PT KAI.      Keywords: PT Kereta Api Indonesia, Human Resources Readiness, Behavior to Change, service orientation.